A15 IMPACT OF DYSFUNCTIONAL MESENCHYMAL TELOCYTES IN THE DEVELOPMENT OF COLITIS ASSOCIATED CANCER. (15th March 2019) - Reyes-Nicolas, V; Pomerleau, V; Garde, P; Boudreau, F; Perreault, N
Abstract: NOT PUBLISHED AT AUTHOR'S REQUEST Funding Agencies: CIHR